PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MATERI JARINGAN KOMPUTER DAN INTERNET PADA MATA PELAJARAN INFORMATIKA KELAS XI MA SEDERAJAT - Khaira Annisak; Meldi Ade Kurnia Yusri; Septriyan Anugrah; Reni Kurnia (STKIP Subang, 2025)
This study aims to develop a multimedia learning application using Microsoft Office PowerPoint for informatics in grade XI MA students, which is considered highly valid and practical. The development stage of this multimedia learning application uses the 4D model, which includes several stages: Define, Design, Develop, and Disseminate. The multimedia learning application developed using Microsoft Office PowerPoint will be tested forfeasibility through validity and practicality tests. The average validation test result from the material and media validators was 92.5, indicating that the multimedia is considered